Pengaruh Good Corporate Governance (GCG), Profitabilitas, dan Leverage Terhadap Nilai Perusahaan - Indriana Damaianti (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2019)
Abstract: The purpose of purpose of this study is to determine the influence of Good Corporate Governance (GCG), profitability, and leverage on firm value in mining companies. This study used secondary data from financial reports, annual reports, and other related information of mining companies listed on Indonesia Stock Exchage (IDX) in the 2014-2018 period. The research method used is the explanatory method. The population in this study were mining companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period, which were 41 companies with total sample 30 companies that matches the criteria. The sampling technique used is a purposive sampling. Data analysis technique used is multiple linear regression. The result showed that only Good Corporate Governance (GCG) variable measured by board of director has a positive and significant effect on the firm value, meanwhile profitability variable measured by Return On Asset (ROA), leverage variable measured by Debt to Equity Ratio (DER), and Good Corporate Governance (GCG) variable measured by board of commissioner independent not significantly impact on the firm value in mining companies.